Colloquium on tax reform in CARICOM countries (CARICOM Secretariat GeorgetownGY, 1987)
Briefly discusses 4 group reports on tax reform and outlines recommendations arising from them. These relate to simplicity, equity, incentive, tax administration, tax relief, real property taxation, revenue management and taxation education programmes. Contains papers presented at the colloquium which discuss topics such as taxation on various economic entities and activities, tax relief, value added tax, sales and property taxes, and tax administration. Annexes contain lists of participants and resource persons as well as remarks and addresses made during the conference.
IDS